Association between hypertriglyceridemic-waist phenotype and cardiovascular disease: A cohort study and meta-analysis - Zheng, Xiaowei; Ren, Xiao; Jiang, Minglan; Han, Longyang (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between hypertriglyceridemic‑waist (HTGW) phenotype and cardiovascular disease (CVD) remains inconsistent and debatable. We aimed to prospectively investigate the relationship between HTGW phenotype and CVD. Methods and results: We included 8,216 participants from the China Health and Retirement Longitudinal Study. Participants were categorized into four subgroups: NTNW: normal triglyceride levels and normal waist circumference; HTNW: high triglyceride levels and normal waist circumference; NTGW: normal triglyceride levels with enlarged waist circumference; HTGW: high triglyceride levels and enlarged waist circumference. A Cox proportional hazards model was applied to determine the association between HTGW phenotype and CVD. A meta-analysis was conducted to incorporate the results of the current study and previous related studies on the association of HTGW phenotype and CVD. In present cohort study, compared to the NTNW phenotype, those with NTGW (HRs 1.34, 95%CIs 1.16-1.55) and HTGW (HRs 1.37, 95%CIs 1.16-1.62) phenotype were significant associated with CVD risk. The meta-analysis further confirmed the significant association between HTGW phenotype and CVD (the pooled relative risk for HTGW vs NTNW was 1.39(1.29-1.49)). Conclusion: The HTGW phenotype was associated with increased risk of CVD, independently of established risk factors. Simple assessment of HTGW phenotypes might help to identify individuals with high‑risk of developing CVD.